Crise e dissolução da forma social: utopia sobre ruínas - elementos do colapso brasileiro da modernização - Frederico Rodrigues Bonifácio (2023)
This thesis departs from contemporary right-wing radicalism, especially in its Bolsonarist expression, and through four interconnected essays, takes as its object the modern social form – understood as a “patriarchal society producing commoditie” (Scholz) –, assuming as a moment the catastrophic dissolution of that social form itself, particularly in its expression in the immediate periphery of capitalist modernization. A movement that allows us to inquire about the “place” of utopian thought in the “collapse of modernization” (Kurz). It operates with the national as a level of analysis – notably in view of what we present as the “Brazilian collapse of modernization” –, not to restore the positivity of the national as a form of capitalist modernization in itself, but precisely in the attempt to understand it as decisive in the formation of an appearance without which the utopian-concrete horizon of modernization itself could not be set. From the presentation of the critical constellation that provides us with the dialectical images of the dissolution of the social form, especially in the Brazilian particularity, we engage in a “critical archeology of exhausted modernization” (Kurz) thinking in retrospect the foundations of what contemporaneity allows to experience as barbarism and dissolution of the future. In this constellation, the new radicalism of the Brazilian right is apprehended not as an atrocious return to the night of the times, but as the very catastrophic becoming of the social form in the historical moment of its disintegration; the so-called necropolitics (Mbembe), is understood within the scope of a critique of the political economy of a collapsing society, and the crisis of the Brazilian economy in the 21st century is interpreted within the scope of the global crisis of the value form. The route also revisits the history of Brazilian social formation, seeking to demonstrate the links between utopian thought, often messianic, with the ideals of progress and modernization.